2015
DOI: 10.1530/endoabs.38.ja5
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous ACTH on circadian aldosterone rhythm in patients with primary aldosteronism

Abstract: We recently reported that stimulation with high-dose ACTH caused different responses in terms of aldosterone secretion in aldosterone-producing adenomas (APAs) and idiopathic hyperaldosteronism (IHA) in patients with primary aldosteronism (PA). However, the role of endogenous ACTH in aldosterone secretion in PA has not been systematically evaluated. In this study, we examined diurnal changes in plasma aldosterone concentration (PAC), and changes in PAC after dexamethasone administration in patients with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This suggests that aldosterone secretion in APA patients is more strongly dependent on endogenous ACTH than in IHA patients. [14][15][16][17] Indeed, aldosterone synthesis and secretion are regulated by ACTH stimulation, 18,19 and aldosterone secretion stimulated by ACTH via the ACTH receptor (MC2R) occurs by a coupled interaction between cAMP and Ca 2+ pathways as an acute secretion process. [18][19][20][21] Importantly, some reports have showed that MC2R overexpression is mainly observed in APA.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that aldosterone secretion in APA patients is more strongly dependent on endogenous ACTH than in IHA patients. [14][15][16][17] Indeed, aldosterone synthesis and secretion are regulated by ACTH stimulation, 18,19 and aldosterone secretion stimulated by ACTH via the ACTH receptor (MC2R) occurs by a coupled interaction between cAMP and Ca 2+ pathways as an acute secretion process. [18][19][20][21] Importantly, some reports have showed that MC2R overexpression is mainly observed in APA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with angiotensin II and potassium, ACTH stimulates aldosterone secretion acutely but transiently ( 31 , 47 ). Aldosterone production follows a circadian rhythm that parallels that of ACTH both in normal individuals, as well as in patients with PA ( 48 , 49 ). In patients with aldosterone-secreting tumors, plasma aldosterone concentration starts to fall around mid-morning, as ACTH levels decrease, in spite of upright posture ( 39 ).…”
Section: Discussionmentioning
confidence: 97%
“…The relative impact of ACTH on aldosterone production from APA vs. BHA and normal ZG cells remains incompletely understood. Small studies suggest that APAs might be more sensitive to ACTH stimulation and suppression than BHA and normal adrenals ( 49 ). Asian studies ( 50 52 ) indicated that the response of aldosterone to cosyntropin stimulation, with or without a priori overnight suppression with 1mg dexamethasone, is higher in patients with APA than in those with BHA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported that ACTH administration produced higher aldosterone concentrations in patients with PA compared with normal controls or patients with essential hypertension . Diurnal increase of aldosterone in early morning and abolition of diurnal rhythm by dexamethasone confirms the role of endogenous ACTH as an important aldosterone secretagogue in PA . Of note, Kobayashi and colleagues showed that early morning systolic BP was correlated with ACTH .…”
mentioning
confidence: 88%